The Relationship between Classroom Emotional Climate (CEC) and Biology Learning Outcomes in the Independent Curriculum at SMAN Kota Tangerang Selatan - Fadilah, Hilmi Gebyar; Zulfiani, Zulfiani (Journal of Educational Sciences, 2025)
This research aims to analyze class emotional climate relationships and how it significantly contributes to affecting learning outcomes at SMAN Kota Tangerang Selatan. The method research used is through survey by leveraging correlational technique. In total, there are 93 students as sample from seven different schools that took probability sampling technique with the kind of cluster sampling. Data gathering on this research is taking questionnaire called Classroom Emotional Climate (CEC) and the biology learning study document called Final Exam as instrument. The research outcomes showed positive, significant, and intense relationship between classroom emotional climate and the biology learning outcomes. Classroom emotional climate influencing 35.28% towards biology learning outcomes and the rest were affected by others. Classroom emotional climate stage and biology learning outcomes are at the middle level with each are graded 73.57% and 71.49%